Police Community Support Officers cultures and identities within pluralized policing - O'Neill, Megan 1974- (Clarendon studies in criminology, 2019)
Police Community Support Officers: Cultures and Identities within Pluralised Policing presents the first in-depth ethnographic study of Police Community Support Officers (PCSOs) since the creation of the role in 2002. Situated within the tradition of police ethnographies, this text examines the working worlds of uniformed patrol support staff in two English police forces. Based on over 350 hours of direct observation and 33 interviews with PCSOs and police constables in both urban and rural contexts, Police Community Support Officers offers a detailed analysis of the operational and cultural realities of pluralised policing from within. 0Using a dramaturgic framework, the author finds that PCSOs have been undermined by their own organisations from the beginning, which has left a lasting legacy in terms of their relationships and interactions with police officer colleagues. The implications of this for police cultures, community policing approaches and the success of pluralisation are examined. The author argues that while PCSOs can have similar occupational experiences to constables, their particular circumstances have led to a0unique occupational culture, one which has implications for existing police culture theories. The book considers these findings in light of budget reductions and police reforms occurring across the sector, processes in which PCSOs are particularly vulnerable.